2020
DOI: 10.31933/dijdbm.v1i5.485
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Good Corporate Governance at Pt Axa Mandiri Financial Services

Abstract: Good Corporate Governance (GCG) is a system that organizes and controls a company so that it can form added value for all stakeholders. This study aims to determine the application of GCG at PT AXA Mandiri Financial Services (AMFS) which is a joint venture Conventional Life Insurance company between PT Bank Mandiri (Persero) Tbk and National Mutual International Pty. Limited (AXA). The research method used is descriptive qualitative. The results of this study indicate that PT AMFS has implemented GCG in an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan) Volume 9 (1) 2024, 30-39 E-ISSN 2614-8021, P-ISSN 2548 This is proven by research results from (Khasanah & Sucipto, 2020) which found that there is an insignificant and positive correlation between the implementation of corporate governance and company value (Tjia, 2020). This is because the company already has corporate governance, but its implementation is still not implemented optimally by the company in accordance with the principles of Good Corporate Governance (GCG).…”
Section: A Introductionmentioning
confidence: 91%
“…JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan) Volume 9 (1) 2024, 30-39 E-ISSN 2614-8021, P-ISSN 2548 This is proven by research results from (Khasanah & Sucipto, 2020) which found that there is an insignificant and positive correlation between the implementation of corporate governance and company value (Tjia, 2020). This is because the company already has corporate governance, but its implementation is still not implemented optimally by the company in accordance with the principles of Good Corporate Governance (GCG).…”
Section: A Introductionmentioning
confidence: 91%
“…Good Corporate Governance has been widely studied by previous researchers including: (Tjia, 2020), (Hamonangan & Hermawan, 2020).…”
Section: Literature Review Good Corporate Governancementioning
confidence: 99%
“…Tata kelola perusahaan yang baik juga disebut sebagai tindakan transparansi atas penentuan tujuan perusahaan, pencapaiannya dan penilaian kinerjanya. Tata kelola perusahaan yang baik bisa dilihat dari budaya pengendalian internal yang kuat, misalnya dari fungsi audit internal yang dimana sumber risiko internal dan eksternal yang berharga serta tidak boleh dilakukan oleh audit internal (Tjia, 2020). Dimensi dari Good Corporate Governance (GCG) adalah: Efisiensi, Responsif, Akuntabilitas, Keadilan dan Pertanggungjawaban (Sadubun, 2020).…”
Section: Good Corporate Governanceunclassified